Reliability of Videoconferencing Administration of a Communication Questionnaire to People With Traumatic Brain Injury and Their Close Others. Issue 6 (November 2017) - Rietdijk, Rachael; Power, Emma; Brunner, Melissa; Togher, Leanne
Abstract : Objectives: To compare in-person with videoconferencing administration of a communication questionnaire for people with traumatic brain injury (TBI) and their close others. Design: Repeated-measures design with randomized order of administration. Participants: Twenty adults with severe TBI and their close others. Methods: Both participants with TBI and their close others completed the La Trobe Communication Questionnaire (LCQ) via interview with a clinician, once via Skype and once during a home visit. Measures: Total LCQ score and time taken for completion. Results: There were no significant differences between videoconferencing and in-person conditions in the total scores or time taken to complete the questionnaire. Conclusions: Videoconferencing-based administration of the LCQ is as reliable and efficient as in-person administration.